IDENTIFICATION OF DETERMINANT FACTOR THE PRICE WOOD OF Rhizophora sp. IN TEMBILAHAN SUB-DISTRICT OF INDRAGIRI HILIR DISTRICT - M. Rizky Fadlian; Evi Sribudiani; M. Mardhiansyah (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2018)
Mangrove (Rhizophora sp.) is one of timber forest products that have long been used and marketed traditionally in Tembilahan Subdistrict. Wood of Rhizophora sp. is utilized because it has use value needed by the inhabitants as a raw material for building construction. The high need for wood of Rhizophora sp. while the use value is still low leads to continuous exploitation. This research is conducted as a basis to measure how far the inhabitants value the existence wood of Rhizophora sp., especially in Tembilahan district through identification of determinants wood of Rhizophora sp. price. The purpose of this research is to identify the determinants factor wood of Rhizophora sp. prices in the market of District Tembilahan Indragiri Hilir. The approach being used in this research is Descriptive Qualitative analysis method. Data were obtained from in-depth interviews, field observations and document studies. Informant retrieval was done by Snowball Sampling and Census. The selling price wood of Rhizophora sp. offered to consumers varies considerably. The selling price wood of Rhizophora sp. in Tembilahan sub-district is determined by the interaction of demand and supply in the market. The traders wood of Rhizophora sp. in Tembilahan sub-district are the price taker and the established markets are perfect competitive markets